EVIDENCE-BASED METHODOLOGY ON STUDYING STUDENTS’ LEADERSHIP SKILLS - Panchenko, Ielyzaveta (Studies in Comparative Education, 2022)
The article is devoted to the research of forming high school students’ leadership skills. To find proper methods and to model the research design, the author based on four assumptions: ontology, epistemology, methodology and methods. On the stage of ontology, the researcher viewed leadership from the stand-point of constructivism where there is no single reality, but there is an existence of multiple realities constructed by individuals. On epistemology level the researcher placed the target object on the continuum closer to interpretivism, as it doesn’t see direct knowledge as possible, claiming that accounts and observations of the world that provide indirect indications the phenomena, thus knowledge can be achieved by means of interpretation. Developing the notion of the continuum, to the left (under realist ontology/positivism epistemology) is nomothetic (seeks to produce general statements that account for larger social patterns, which form the context of single events, individual behaviors, and experience) and experimental in nature. To the right (under constructivism ontology/interpretivism epistemology) is ideographic, dialectical and hermeneutical in nature. So we are to use the latter ones. At the forth level mixed methods were chosen with some quantitative and qualitative ways of data collection. The advantages of mixed methods at general, practical and procedural levels are described. To model a research design, the author studied and used 5 types of triangular-tion: time triangulation, research target group synchronically and diachronically; space triangulation – take into consideration leadership goals of Ukrainian stu-dents, comparing to the ideal American leader; combined levels of triangulation can help us analyze the leadership from three principal levels used in social sciences: individual level, interactive/group level, and the level of collectives; theoretical triangulation, describing alternative or competing approaches/theories of leadership; investigator triangulation - all the people involved in summer school will take part in data collection that will influence final results and make them more objective.